Pengaruh Kualitas Produk dan Citra Merek terhadap Keputusan Pembelian Sepeda Motor Merek Honda Scoopy Pada PT. Sentosa Sakti Motor Thehok Jambi - Bastian Praswara (Science of Management and Students Research Journal (SMS), 2022)
Several automotive companies which relatively dominate the market compete with each other to attract the purchasing decisions of consumers who buy motorcycle products. Purchase decisions are consumer decisions regarding preferences for brands in the choice set. Purchase decisions can be influenced by several factors such as product quality and brand image. The purpo se of this study was to describe product quality, brand image, and purchasing decisions for Honda Scoopy motorcycles at PT. Sentosa Sakti Motor Thehok and to analyze the effect of product quality and brand image on purchasing decisions for Honda Scoopy motorcycles at PT. Sentosa Sakti Motor Thehok. The research method used in this research is descriptive and quantitative methods. Methods of data collection is done by observation and questionnaires. The sample was searched using the Slovin formula so that a sample of 88 respondents  was  obtained.  Data  analysis  was  carried  out  by  descriptive  analysis  and  quantitative  analysis,  namely  Multiple Regression Analysis. Based on the results of the study indicate that the descriptive variables of product quality, brand image, and purchasing decisions are categorized as high. Validity and reliability tests are met so that the questionnaire can be used. The data meet the regression assumption test. Multiple linear regression model was obtained as follows: Y = 2.718 + 0.220X1 + 0.705X2 Based on the regression model obtained, it shows that if the product quality and brand image are increasing, it will also inc rease the decision to purchase Honda Scoopy motorcycles at PT. Sentosa Sakti Motor Thehok. The results of hypothesis testing indic ate that the variables of product quality and brand image have an effect on purchasing decisions partially or simultaneously. Adjusted R Square of 0.445, meaning that 44.5% of product quality and brand image affect purchasing decisions.